2022
DOI: 10.1186/s12879-022-07339-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of second-line drug resistance among drug resistant tuberculosis patients tested in Uganda: a two and a half-year’s review

Abstract: Background Second-line drug resistance (SLD) among tuberculosis (TB) patients is a serious emerging challenge towards global control of the disease. We characterized SLD-resistance conferring-mutations among TB patients with rifampicin and/or isoniazid (RIF and/or INH) drug-resistance tested at the Uganda National TB Reference Laboratory (NTRL) between June 2017 and December 2019. Methods This was a descriptive cross-sectional secondary data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…These results were relatively concordant to another study conducted in India on 90 M. tuberculosis clinical isolates to correlate rrs and eis promoter mutations with phenotypic susceptibility levels toward the injectables of the second-line using GenoType MTBDRsl assay (Hain LifeScience GmbH, Germany), the agreement of results was 97% for AMK, 96% for KM and 86% for CM 21 . Our results exceeded the results of another Line Probe Assay (LPA) currently proposed by WHO for the early drug resistance screening of sputum smear-positive samples; GenoType MTBDRplus VER2.0, which displays inconstant sensitivity and specificity for the screening of resistance to injectable SLDs 22, 23 . The overall specificity ranging from 59 to 100% and sensitivity from 83 to 87% for identifying XDR isolates 24, 25 .…”
Section: Discussioncontrasting
confidence: 58%
“…These results were relatively concordant to another study conducted in India on 90 M. tuberculosis clinical isolates to correlate rrs and eis promoter mutations with phenotypic susceptibility levels toward the injectables of the second-line using GenoType MTBDRsl assay (Hain LifeScience GmbH, Germany), the agreement of results was 97% for AMK, 96% for KM and 86% for CM 21 . Our results exceeded the results of another Line Probe Assay (LPA) currently proposed by WHO for the early drug resistance screening of sputum smear-positive samples; GenoType MTBDRplus VER2.0, which displays inconstant sensitivity and specificity for the screening of resistance to injectable SLDs 22, 23 . The overall specificity ranging from 59 to 100% and sensitivity from 83 to 87% for identifying XDR isolates 24, 25 .…”
Section: Discussioncontrasting
confidence: 58%
“…44 In our study, a single isolate was detected in the gyrA gene with a common mutation at codon D94G associated with FQ-resistant isolates, but the high prevalence of gyrA mutations has been well described in different regions. 2,7,34,45 This could be due to the low prevalence of FQ-resistant isolates in our study because of the insufficient sample size used. Besides, no mutations in the gyrB gene conferring resistance to FQs, rrs, or eis genes causing SLIDs were observed in our study.…”
Section: Discussionmentioning
confidence: 91%
“…23 It was also realized that MTBDRsl could aid in real-time surveillance of emerging DR-TB, both pulmonary and EPTB, in endemic country like India. 24 The present study, to the best of our knowledge, is the first to evaluate the performance of MTBDRplus and MTBDRsl for detecting presence and pattern of drug resistance in a decent cohort of 30 cases of GITB. Both MTBDRplus and MTBDRsl, in the current study, gave positive band for M. tuberculosis in all 30 specimens, and no false negative or invalid results were obtained.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies on pulmonary TB revealed that MTBDR assays reduced the proportion of “empirical therapy” patients and boosted up targeted therapy with improvement in DR‐TB management 23 . It was also realized that MTBDRsl could aid in real‐time surveillance of emerging DR‐TB, both pulmonary and EPTB, in endemic country like India 24 . The present study, to the best of our knowledge, is the first to evaluate the performance of MTBDRplus and MTBDRsl for detecting presence and pattern of drug resistance in a decent cohort of 30 cases of GITB.…”
Section: Discussionmentioning
confidence: 99%